Repetitive transcranial magnetic stimulation regulates neuroinflammation in neuropathic pain - Bai, Yi-Wen; Yang, Qi-Hao; Chen, Pei-Jie; Wang, Xue-Qiang (Frontiers in Immunology, 2023)
Neuropathic pain (NP) is a frequent condition caused by a lesion in, or disease of, the central or peripheral somatosensory nervous system and is associated with excessive inflammation in the central and peripheral nervous systems. Repetitive transcranial magnetic stimulation (rTMS) is a supplementary treatment for NP. In clinical research, rTMS of 5–10 Hz is widely placed in the primary motor cortex (M1) area, mostly at 80%–90% RMT, and 5–10 treatment sessions could produce an optimal analgesic effect. The degree of pain relief increases greatly when stimulation duration is greater than 10 days. Analgesia induced by rTMS appears to be related to reestablishing the neuroinflammation system. This article discussed the influences of rTMS on the nervous system inflammatory responses, including the brain, spinal cord, dorsal root ganglia (DRG), and peripheral nerve involved in the maintenance and exacerbation of NP. rTMS has shown an anti-inflammation effect by decreasing pro-inflammation cytokines, including IL-1β, IL-6, and TNF-α, and increasing anti-inflammation cytokines, including IL-10 and BDNF, in cortical and subcortical tissues. In addition, rTMS reduces the expression of glutamate receptors (mGluR5 and NMDAR2B) and microglia and astrocyte markers (Iba1 and GFAP). Furthermore, rTMS decreases nNOS expression in ipsilateral DRGs and peripheral nerve metabolism and regulates neuroinflammation.